Hubungan Logistik Terhadap Pertumbuhan Ekonomi: Studi Kasus 9 Negara Emerging Markets Asia - Helmi Arafat Priyajati; Tri Haryanto (Trunojoyo University of Madura, 2020)
The logistics sector is an important link of increasing international trade, increasing competitiveness and playing an important role in economic growth and the country's economic development. This study aims to determine the impact of the development of the logistics sector on economic growth. In this study the logistics sector has indicators of capital stock, air transportation, railways, shipp, internet users, warehousing and employment in Asian emerging markets countries in 2005-2017. The data used in this study are secondary data originating from the World Bank which is processed by the panel data regression method. Based on the estimation results, the results obtained together with variables of capital stock, air transportation, railways, shipp, internet users, warehousing and employment have a significant effect on economic growth. While partially the variables of capital stock, air transportation, railways, shipp, internet users, warehousing and employment connectivity have a significant positive effect on economic growth in Asian emerging market countries.